Embedding MnO2 Ultrafine Nanoparticles within Graphene‐Based Hybrid Elastomer as an Anode for Enhanced Lithium Storage. Issue 16 (4th July 2018) - Zhou, Xiangyang; Cheng, Fangyan; Tang, Jingjing; Sun, Antao; Bai, Tao; Yu, Yawen; Yang, Juan
Abstract: Despite its high theoretical capacity, the practical application of MnO2 anodes for lithium‐ion batteries is still hindered by poor rate capability, owing to its low electronic conductivity and large volume variation during Li + insertion/extraction. Herein, these tough issues are tackled by embedding MnO2 ultrafine nanoparticles within polydopamine‐modified reduced graphene oxide. This smart design skillfully utilizes the reduction and self‐polymerization properties of dopamine to reduce graphene oxide while MnO2 ultrafine nanoparticles are embedded in the polydopamine and form a stable interface. The polydopamine, acting as an elastomer, can cushion the stress associated with the expansion of MnO2 ultrafine nanoparticles, and the reduced graphene oxide, as the highly conductive matrix, can greatly improve the rate performance. The resultant composites exhibit a high reversible capacity, excellent cycling stability, and good rate performance, owing to the synergistic effects among conductive graphene, elastic polydopamine, and ultrafine MnO2 . Abstract : Wrap up : T‐MnO2 ultrafine nanoparticles (3–5 nm) are embedded within polydopamine (PDA)‐wrapped reduced graphene oxide (T‐MnO2 /rGO@PDA). The T‐MnO2 /rGO@PDA composite is synthesized by using a straightforward wet chemical method. This unique design endows the composite with excellent performance. A high reversible capacity of 571 mA h g −1 at 1000 mA h g −1 can be sustained after 600 cycles.